Transgenic expression of the Arabidopsis DELLA proteins GAI and gai confers altered gibberellin response in tobacco. - Hynes, L; Peng, J; Richards, D; Harberd, N (2003)
Bioactive gibberellin (GA) regulates the growth and development of a wide array of plant species. GA exerts its effects via members of the DELLA protein family of putative transcriptional regulators. The GAI gene encodes GAI, a DELLA protein from Arabidopsis thaliana (L.) Heyhn. A mutant allele, gai, encodes a mutant protein (gai) that has altered properties, and confers a dominant, reduced GA-response, dwarf phenotype. Here we describe experiments to investigate the effects of transgenic expression of GAI and gai in tobacco. Constructs permitting the expression of the GAI and gai open reading frames (ORFs) at higher (driven by the cauliflower mosaic virus 35S promoter) and lower (driven by the original Arabidopsis GAI promoter) levels in tobacco were made. We show that low-level expression of GAI has no detectable effect on tobacco GA-responses. In contrast, high-level expression of GAI clearly affects the growth of adult tobacco plants and the GA-responsiveness of tobacco hypocotyls. Both low- and high-level expression of gai have effects on tobacco GA responses. Thus, tobacco GA-responses are affected by transgenic expression of GAI/gai, and the degree to which these responses are affected is related to the level of transgene expression.